ADOPTING AN OPEN SOURCE HOSPITAL INFORMATION SYSTEM TO MANAGE HEALTHCARE INSTITUTIONS - Bouidi, Youssef; Azzouzi Idrissi, Mostafa; Rais, Noureddine (LIFE: International Journal of Health and Life-Sciences, 2017)
Our paper is a comparative study of different Open Source Hospital Information Systems (OSHISs). We chose open source because of problems in healthcare management like budget, resources and computerization. A literature review did not allow us to find a similar comparison, which explains the great interest of our study. Firstly, we retrieved nine OSHISs: MediBoard, OpenEMR, OpenMRS, OpenHospital, HospitalOS, PatientOS, Care2x, MedinTux and HOSxP. Then, we used the DeLone & McLean model to evaluate information systems qualities and the SQALE method for the technical evaluation. Finally, we get OSHISs activities using open source community statistics. In application, we used SonarQub as a SQALE implementation. As results, we get six characteristics for MediBoard (respectively OpenEMR, OpenMRS, OpenHospital, HospitalOS, PatientOS, Care2x, MedinTux and HOSxP), with a technical debt of 42.16% (respectively 53.23%, 54.5%, 65%, 66.1%, 65.2%, 56.96%, 52.13% and 75.5%). Activities statistics prove the MediBoard potential with 2381 commits and 12 contributions in 2016. Based on these results, we chose MediBoard as a solution to adapt in healthcare organizations. It is also a challenge to prove open source power in health management. As a future work, we will implement and test MediBoard modules in a real case.